Tax Fairness and Public Perception: A Comparative Literature Review - Naslia, Fifi Angriani Putri; Yulianti, Yulianti (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the complex dynamics that shape tax justice perceptions and compliance behavior, considering individual, institutional, and contextual factors. Research Design and Methodology: Using comparative literature review methodology, this research synthesizes findings from studies across multiple disciplines, including economics, psychology, and political science. Findings and Discussion: The findings show that socio-economic status, political ideology, cultural values, and institutional trust significantly influence individuals' attitudes towards taxation and compliance with tax laws. The research also highlights the importance of transparency, accountability, and responsiveness in tax administration in building trust and encouraging compliance. Implications: By leveraging technological advances, enhancing international cooperation, and implementing progressive tax reforms, stakeholders can work towards creating a fairer and more equitable tax system that supports social cohesion and economic prosperity.